TAX EXCHANGE OF INFORMATION AND INTERNATIONAL COOPERATION IN BRAZIL* - Estellita, Heloisa [UNESP]; Bastos, Frederico Silva (Fundação Getúlio Vargas, Escola de Direito, 2015)
Globalization and internationalization of companies are phenomena that need to be considered by modern tax administrations. In many situations, such as tax evasion, harmful tax competition and money laundering, domestic statutes seem to be ineffectual in a global dimension. Fo cope with that, new forms of regulation and regulators emerge. Under this view, an effort towards signing international treaties, conventions and agreements seems to be a feasible solution. The brazilian legal framework contains principles and rules that make international cooperation and exchange of information (eoi) with other countries possible. Furthermore, the brazilian tax administration has wide-ranging access powers to obtain information for international exchange purposes and has the tools to coercively produce such information. Brazil is following the right path to implement international exchange of information standards. However, there are some obstacles that need to be fixed for a more efficient implementation of these mechanisms. This article examines some topics of the brazilian legal and institutional framework on the tax exchange of information, such as a new model of approach of the tax administration, the tax transparency agenda and the international agreements on eoi matters, the brazilian supreme court rulings under bank secrecy and the rights of brazilian taxpayers regarding eoi.

A globalização e a internacionalização das empresas são fenômenos que precisam ser considerados pelas modernas administrações tributárias. Fiscalizar e combater a evasão fiscal, o planejamento tributário agressivo e a lavagem de dinheiro somente com medidas domésticas tende a ser inócuo em uma dimensão global. Para lidar com esse cenário, novas formas de regulação e reguladores são exigidas. Sob este ponto de vista, um esforço no sentido de assinar tratados internacionais, convenções e acordos parece ser uma solução viável. O arcabouço legal brasileiro contém princípios e regras que tornam a cooperação internacional e o intercâmbio de informações (eoi) com outros países possíveis. Além disso, a administração tributária brasileira tem amplos poderes de acesso para obter informações para fins de intercâmbio internacional, assim como conta com ferramentas para produzir coercitivamente tais informações. Nesse contexto, o brasil tem realizado grandes esforços para adequar suas instituições e legislações aos padrões internacionais no que tange à troca de informações tributárias. No entanto, existem alguns obstáculos que precisam ser observados para uma execução mais eficaz destes mecanismos. Nesse sentido, este artigo se propõe a analisar algumas questões importantes referentes à moldura jurídica e institucional brasileira no intercâmbio de informações tributárias, tais como, a mudança de paradigma na atuação das administrações tributárias, a agenda da transparência fiscal e os acordos internacionais em matéria eoi, as decisões do supremo tribunal federal sobre o sigilo bancário e os direitos dos contribuintes brasileiros em relação ao eoi.
O INTERCÂMBIO DE INFORMAÇÕES TRIBUTÁRIAS E A COOPERAÇÃO INTERNACIONAL NO BRASIL
Keywords: Globalization; tax evasion; exchange of information; international cooperation; tax administration; Globalização; evasão fiscal; intercâmbio de informações; cooperação internacional; administração tributária